Design and Evaluation of an Autonomous Insect Robot with Integrated Navigation and Communication Systems - Muda, Nur Rachman Supadmana (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This paper presents the design, development, and experimental evaluation of an autonomous insect robot equipped with a long-range camera, GPS module, anti-collision sensors, servo actuators, micro battery, Tx/Rx communication system, and flight control unit. The robot was tested over communication distances ranging from 300 m to 1000 m, with performance assessed in terms of transmission reliability, latency, throughput, GPS accuracy (RMSE), and sensor accuracy. Results show that communication reliability decreases from 98.2% at 300 m to 80% at 1000 m, while throughput drops from 7.96 Mbps to 3.89 Mbps. GPS precision slightly declines from 0.63–0.66 m at shorter ranges to nearly 1.0 m at the farthest distance. Sensor accuracy remains relatively stable within 92–95%, demonstrating robustness of the sensing system. A composite performance score integrating all parameters identified 300 m as the optimal range, with the highest score of 96.3. These findings confirm that insect robots are highly effective for close-to-medium range missions, offering reliable communication, accurate navigation, and robust sensing in compact, energy-efficient form. The study highlights their potential for applications in surveillance, environmental monitoring, and search-and-rescue operations. Future improvements should address extended range, longer endurance, and enhanced autonomy through AI-based flight control and advanced miniaturized sensors.